Peningkatan Prestasi Fisika Siswa Pada Kelas XI Di Mas Darul Ikhlas Padangsidimpuan - Rodiah Ulfah Lubis; Eni Sumanti Nasution (Institut Agama Islam Negeri Padangsidimpuan, 2022)
The sample of this research is MAS Darul Ikhlas Class XI with 30 students. The sampling technique was purposive sampling. The results of the study indicate that between the initial conditions (Pre-Cycle), Cycle I and Cycle II, it can be seen that during the initial conditions the average value of the class was 60.21, while the average value of the first cycle class had increased to 69.79. and in the second cycle it increased sharply to 81.67. The results of the study showed that there was an increase in student’s physics learning achievement after the treatment.